Ammonia-triggered disintegration of kappa-carrageenan hydrogel carrier for site-specific anti-inflammatory drug delivery - Kumar, Sachin; Purohit, Priyank; Panwar, Surbhi; Kharatmal, Shivsharan Balbhim; Munjal, Sachin; Abdellattif, Magda H.; Thotange, Chaitali Anil; Sambhaji mane, Rachana (Frontiers in Bioengineering and Biotechnology, 2026)
Ammonia accumulation in tissues is increasingly recognized as a direct biochemical trigger of ammonia-induced inflammation, yet no therapeutic strategy currently exists that can selectively target this pathological condition while minimizing systemic toxicity. Addressing this critical gap, the present study introduces a first-of-its-kind kappa-carrageenan (KC)-based formulation engineered to respond selectively to ammonia-rich inflammatory environments while simultaneously exerting synergistic anti-inflammatory effects. The KC gel’s structural network exhibited pronounced disruption upon exposure to ammonium hydroxide, supported by physicochemical changes, the weakening of OH and SO3H absorption bands in FT-IR spectra, and optical microscopy-confirmed morphological alterations. Drug-release studies revealed highly accelerated celecoxib release (up to 86%) from NH4OH-treated gels compared to only 33% under normal physiological conditions, demonstrating strong ammonia-triggered responsiveness and high site-selective delivery. In vivo anti-inflammatory evaluation further confirmed enhanced therapeutic potency arising from the synergistic interaction between celecoxib and KC, while cell-line assays validated the formulation’s favorable safety profile. Although long-term stability and pharmacokinetic assessments are required for clinical translation, this study establishes KC as a dual-functional, smart, and ammonia-responsive system, offering a novel mechanistic framework for targeted, sustained, and effective treatment of ammonia-associated inflammatory disorders.